DIGITAL TRANSFORMATION OF THE PUBLIC SECTOR IN UZBEKISTAN: SUCCESSES AND CHALLENGES (Journal of Universal Science Research, 2024)
Digital transformation of the public sector is a key aspect of modernization and economic development in any state. Uzbekistan, striving to integrate into the global economy and improve the quality of life of its citizens, is actively introducing digital technologies into various areas of public administration. This article examines the achievements of Uzbekistan in the field of digitalization of the public sector, as well as the challenges that the country faces along this path.